Crowdsourcing for Online Samples in Counseling Research. (8th March 2021) - Mullen, Patrick R.; Fox, Jesse; Goshorn, Jeremy R.; Warraich, Leila Khalid
Abstract : The use of panels and registration systems for sampling procedures in counseling research offers an innovative method of recruiting participants. Websites such as Amazon's Mechanical Turk, provide quick access to pools of participants for an assortment of research designs. Other sites such as Qualtrics and SurveyMonkey Audience offer tailored and targeted searches and recruitment of specific samples to create online panels. Although these methods of accessing a sample provide ease of access and flexibility of design, there are several cautions to consider when using them for counseling research. In this article, we accomplish several aims: (a) define and describe the concept of crowdsourcing research participation, (b) describe some benefits and cautions about their use, and (c) present different applications of this approach to sampling. We also note the implications of this sampling method for counseling research.